Legislación y personalidad de Justianiano: su matrimonio con Teodora - González Fernández, Rafael (Antigüedad y Cristianismo, 1991)
This is a rewiew of the personal y juridical episode of the marriage of Jestinian, considered until now only from the religious point of view. We have tried to demostrate that not only coincided religious aspects, if one can mención them, but also the desire of Justinian as an individual, disguised as a measure of the Imperial wil. It was a legal decision which benefited only one person, Teodora, who nevertheless gained from all the scenicae.